Effect of Infilled Frames on Reduction Factor (R) for RC Irregular Structure - Mai R. El-Hadary; Mahmoud E. Nasr; Wael El-Badrawy; Nasr E. Nasr (Salehan Institute of Higher Education, 2024)
Investigating the modification factors as a critical seismic design tool, delineating the anticipated level of inelastic behavior within structural systems during seismic events. Both damping and ductility are included in this factor, particularly at movement nearing maximum capacity. Moreover, it offers valuable insights into buildings' response during earthquakes and the anticipated behavior of structures compliant with building codes during design earthquakes. Essentially, it mirrors the structure's capacity to dissipate energy via an inelastic mechanism. In this research, the infill (RC) structures with various structural irregularities were focused. The selected irregularities included dimension, elevation, and mass. Infill location, number of bays, and seismic zone were the expected R factors for RC frames. Non-linear static pushover analysis was adopted in numerical simulation. The available data gathered from the literature was used to validate the outcomes of the developed models. Additionally, the effects of different types of soil were taken into consideration, and the research results demonstrated that the value of the modification factor (R) for change in stiffness and mass of high-rise buildings for bare and infill (RC) structures is less compared to irregular (RC) structures. It was concluded that the same structure with different types of soil and different parameters has a great effect on the value of R for bare and infill regular and irregular (RC) structures. Furthermore, recommendations for accurate R estimation for RC structures were discussed. Doi: 10.28991/CEJ-2024-010-08-09 Full Text: PDF